3-D Morphometric Analysis of Talocalcaneal Joint in Stage II Posterior Tibial Tendon Dysfunction. Issue 3 (14th September 2018) - Cain, Jarrett D.; Lewis, Gregory; Kunselman, Allen
Category: Hindfoot Introduction/Purpose: Posterior Tibial Tendon Dysfunction (PTTD) is common disorder that can lead to changes in function during the gait cycle due to decreased arch, increased hindfoot valgus, and forefoot abduction. These kinematic changes can have a structural impact on the joints throughout the foot. While previous studies have evaluated anatomical three-dimensional (3D) position of the subtalar joint, the purpose of this study was to perform morphological analysis of the anterior, middle and posterior facets in patients with stage II posterior tibial tendon dysfunction compared to normal controls. Methods: Clinical computed tomography images from 10 matched feet (i.e., 10 normal and 10 stage II PTTD) were obtained and used for 3D reconstruction in Mimics software (Materialise). From the3D reconstructions, morphometric evaluations of the subtalar joint were completed including 3D anatomic point placement and measurements of the length and width of the anterior, middle and posterior facets (Fig. 1) by 3 independent evaluators. Evaluators were blinded to experimental groups and to one another's measurements. A linear mixed-effects model was used to assess the differences between control and PTTD subtalar joints with respect to morphometric measurements (mm). The concordance correlation coefficient (CCC) was used to assess the agreement between the 3 evaluators with respect to their recorded morphometric measurements per location (e.g., anterior, middle, posterior). Results: Although the mean distance of the length and width of the middle facet trended higher in the stage II PTTD compared to controls, this difference was not statistically significant (Table 1). Similarly, there was no difference detected between control and PTTD with respect to morphometric measurements in the anterior and posterior facets (Table 1). The agreement among the 3 evaluators with respect to morphometric measurements was the strongest in the length and width of the middle facets. Conclusion: Stage II posterior tibial tendon dysfunction has been shown to cause increase subtalar joint kinematics, joint contact pressure. Based on the results, there is a positive correlation involving morphologic changes of subtalar joint with the middle facet measurements being larger in the PTTD group. Further studies are needed with weight bearing CT scans in correlation with advance stages of posterior tibial tendon dysfunction.